From innate-like to innate: the next wave of off-the-shelf CAR immunotherapies - Feng, Ying; Yang, Zhibo; Zhou, Yueru; Liang, Ying; Zhao, Hai (Frontiers in Immunology, 2026)
While autologous CAR T-cell therapies have revolutionized the treatment of hematologic malignancies, their widespread application is hindered by manufacturing complexities, high costs, and limited efficacy against solid tumors due to antigen heterogeneity and the TME. Moreover, the logistical burden of bespoke patient-specific manufacturing restricts global scalability. In response, the immunotherapy landscape is pivoting toward “off-the-shelf” allogeneic therapies derived from innate and innate-like effectors. This review provides a comprehensive analysis of four emerging platforms: CAR-NK cells, CAR-NKT cells, γδ T cells, and CAR-M. Unlike conventional αβ T cells, these lineages utilize MHC-independent mechanisms to recognize stress-induced ligands or lipid antigens, inherently minimizing the risk of GvHD while enabling standardized, batched manufacturing. We critically examine the diverse manufacturing paradigms, contrasting the scalability of iPSC-derived sources with the accessibility of umbilical cord blood products. Furthermore, we detail advanced engineering strategies designed to overcome the lineage-specific limitations revealed by early trials—specifically, “armoring” constructs with IL-15 to boost in vivo persistence and metabolic reprogramming to sustain function within the TME. Finally, we synthesize emerging clinical evidence which confirms the favorable safety profile of these allogeneic approaches but highlights persistent bottlenecks: limited durability of response, cryopreservation-induced loss of viability, and batch-to-batch variability. We conclude that unlocking the full potential of innate CAR therapies requires a dual focus on harmonizing manufacturing controls and developing next-generation engineering logic to ensure durable control of solid tumors.